L’Idée latine du Félibrige et la Renaissance romanche 1874-1914 - Bettina Berther Desax (Revue des Langues Romanes)
From 1874 onwards, the RLaR regularly published Romansh literary texts, often accompanied by studies on this minority Romansh language spoken in the Swiss Alps. In this period of literary and linguistic revival of Occitan language, the Romansh Renaissance movement followed the example of the Félibres. It was in the spirit of Latin Idea that the Félibres and the representatives of the Romansh Renaissance maintained a mutual relationship. Relations with Engadine began in 1874 with Roque-Ferrier’s “Un Recueil de poésies rumonches”, published in the RLaR, then reached a peak in 1882 with the participation of the Romansh writer Gian Fadri Caderas in the Jeux Floraux de Forcalquier, and eventually declined after his death. A relationship between Provence and Surselva was established by Caspar Decurtins and Frédéric Mistral, which was in full swing thanks to the publication of several articles on the two languages and several translations from Romansh into Occitan and vice versa by Flurin Camathias and Jules Ronjat. In this way, regional questions took on an international dimension.